Mutation in Irf8 Gene (Irf8R294C) Impairs Type I IFN-Mediated Antiviral Immune Response by Murine pDCs - Das, Annesa; Chauhan, Kuldeep Singh; Kumar, Himanshu; Tailor, Prafullakumar (Frontiers in Immunology, 2021)
Plasmacytoid dendritic cells (pDCs) are the key producers of type I interferons (IFNs), thus playing central role in initiating antiviral immune response. Besides robust type I IFN production, pDCs also act as antigen presenting cells post immunogenic stimulation. Transcription factor Irf8 is indispensable for development of both pDC and cDC1 subset. However, the mechanism underlying the differential regulation by IRF8 in cDC1 and pDC specific genomic architecture of developmental pathways still remains to be fully elucidated. Previous studies indicated that, the Irf8R294C mutation specifically abrogates development of cDC1 without affecting that of pDC. In present study using RNA-seq based approach, we have found that though the point mutation Irf8R294C does not affect pDC development, it leads to defective type I IFN production, thus resulting in inefficient antiviral response. This observation unravels the distinctive roles of IRF8 in these two subpopulations- regulating the development of cDC1 whereas modulating the functionality of pDCs without affecting development. We report here, Irf8R294C mutation also causes defect in production of ISGs, prevents pDC activation in response to NDV infection (or CpG stimulation). Through in vivo studies, we demonstrate that abrogation of type I IFN production was concomitant with absence of pDC activation and increased NDV burden in IRF8R294C mice in comparison with wild type indicating inefficient viral clearance. Further we have also shown that Irf8R294C mutation abolishes the activation of type I IFN promoter by IRF8 justifying the low level of type I IFN production. Taken together, our study signifies that the single point mutation in Irf8, Irf8R294C severely compromises type I IFN mediated immune response by pDCs, thereby causing impairment in antiviral immunity.